2003
DOI: 10.1520/jfs2002079
|View full text |Cite
|
Sign up to set email alerts
|

A Classifier for the SNP-Based Inference of Ancestry

Abstract: Ancestral inference from DNA could serve as an important adjunct for both standard and future human identity testing procedures. However, current STR methods for the inference of ancestral affiliation have inherent statistical and technical limitations. In an effort to identify biallelic markers that can be used to infer ancestral affiliation from DNA, we screened 211 SNPs in the human pigmentation and xenobiotic metabolism genes. Allele frequencies of 56 SNPs (most from pigmentation genes) were dramatically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 16 publications
1
44
0
2
Order By: Relevance
“…When we adjusted the data for the locus on chromosome 15q and performed a new genomescan (data not shown), the next largest test statistics were LODs of 1.7 and 1.5, on chromosomes 12 and 11, respectively, which were slightly higher LOD scores than seen in the scan unadjusted for the 15q locus. Although these were not significant at the genome-wide level, the chromosome 11 peak is interesting as it is in a region that contains the tyrosinase gene (TYR, aka OCA1A on 11q14-11q21) which plays a role in melanine formation in the eye (Frudakis et al, 2003;Oetting and King, 1993). The same regions on 11 and 12 showed modest peaks in the analysis of Zhu et al, 2004. The regression method is robust and because it is extremely fast it lends itself to computer-intensive resampling methods such as permutation testing to obtain significance and for example bootstrapping to estimate the confidence region of the trait locus.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When we adjusted the data for the locus on chromosome 15q and performed a new genomescan (data not shown), the next largest test statistics were LODs of 1.7 and 1.5, on chromosomes 12 and 11, respectively, which were slightly higher LOD scores than seen in the scan unadjusted for the 15q locus. Although these were not significant at the genome-wide level, the chromosome 11 peak is interesting as it is in a region that contains the tyrosinase gene (TYR, aka OCA1A on 11q14-11q21) which plays a role in melanine formation in the eye (Frudakis et al, 2003;Oetting and King, 1993). The same regions on 11 and 12 showed modest peaks in the analysis of Zhu et al, 2004. The regression method is robust and because it is extremely fast it lends itself to computer-intensive resampling methods such as permutation testing to obtain significance and for example bootstrapping to estimate the confidence region of the trait locus.…”
Section: Discussionmentioning
confidence: 98%
“…Frudakis et al (2003) used a hypothesis-driven SNP screen, focusing on pigmentation candidate genes. They identified 61 SNPs that were associated with iris pigmentation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of several collections of cases and controls with different origin, as performed here, will allow the identification of these situations. When the available population has an admixed origin the use of markers for inference of ancestry [35][36][37] could be useful as has been shown recently by the development of a panel of SNP markers that differentiate between Europeans from the South and from the North. 21 …”
Section: Discussionmentioning
confidence: 99%
“…21 Human eye colour is a fully genetically determined trait with a 22 complex inheritance pattern, although most times it apparently 23 behaves as a simple Mendelian character. This is so because one 24 genetic region, HERC2/OCA2, accounts for the majority of the blue 25 and brown variation (the two most common colours) in human 26 eye colour [2,3]. 27 Although genetic association studies had already identified the 28 relationship between the OCA2 gene and eye colour [2,4], it was not 29 until 2008 when three independent studies found that HERC2, a 30 neighbouring gene, and specifically the SNP rs12913832, was the 31 key human eye colour regulator [5][6][7].…”
mentioning
confidence: 99%
“…This is so because one 24 genetic region, HERC2/OCA2, accounts for the majority of the blue 25 and brown variation (the two most common colours) in human 26 eye colour [2,3]. 27 Although genetic association studies had already identified the 28 relationship between the OCA2 gene and eye colour [2,4], it was not 29 until 2008 when three independent studies found that HERC2, a 30 neighbouring gene, and specifically the SNP rs12913832, was the 31 key human eye colour regulator [5][6][7]. In addition, other genes 32 such as SLC24A4, SLC45A2, TYR, TYRP1, ASIP or IRF4 have also been 33 recognised to contribute to eye colour variation, although to a 34 much lesser extent [8][9][10].…”
mentioning
confidence: 99%